Mild Exercise Rescues Steroidogenesis and Spermatogenesis in Rats Submitted to Food Withdrawal - Santillo, Alessandra; Giacco, Antonia; Falvo, Sara; Di Giacomo Russo, Federica; Senese, Rosalba; Di Fiore, Maria Maddalena; Chieffi Baccari, Gabriella; Lanni, Antonia; de Lange, Pieter (Frontiers in Endocrinology, 2020)
The present investigation was undertaken to increase our insight into the molecular basis of the physiological changes in rat testis induced by food withdrawal, and to clarify whether reduced testicular function can be ameliorated by mild exercise. Male rats were selected for four separate experiments. The first of each group was chow-fed, the second was chow-fed and submitted to exercise (5 bouts in total for 30 minutes at 15 m/min, and 0° inclination), the third was submitted to food withdrawal (66h) and the fourth was submitted to food withdrawal and to exercise. At the end of experiments, we investigated (i) serum and testicular sex hormone levels; (ii) protein levels of StAR, 3β-Hydroxysteroid dehydrogenase (3β-HSD) and P450 aromatase, which play a key role in steroid hormone biosynthesis; and (iii) protein levels of mitotic and meiotic markers of spermatogenesis in rats, in relation to testis morphology and morphometry. We found that mild exercise or food withdrawal alone induced a significant increase or decrease in both serum and testis testosterone levels, respectively. Interestingly, we found that these levels were brought back to basal levels when food withdrawal was combined with mild exercise. The changes in testosterone levels observed in our experimental groups correlated well with the expression of steroidogenic enzymes as well as with spermatogenic activity. With mild exercise the increased testosterone/17β-estradiol (T/E2) ratio in the testis correlated with an increased spermatogenic activity. The T/E2 ratio dropped in fasted rats and was significantly reversed when food withdrawal was combined with exercise. Histological and morphometric analyses confirmed that spermatogenic activity varied in concomitance with each experimental condition. Importantly, the testis and serum T/E2 ratios correlated, confirming that exercise rescues the decline in food withdrawal-induced spermatogenesis. In conclusion, this study highlights that mild exercise normalizes the reduced spermatogenic activity caused by food withdrawal through the modulation of the steroidogenic pathway and restoring the T/E2 ratio, underlining the beneficial effects of mild exercise on the prevention and/or amelioration of reduced testis function caused by restricted caloric intake.